Perancangan Galeri Fotografi Dengan Pendekatan Arsitektur Metafora - Nazamri Nazamri; Gun Faisal; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The photography gallery is a place to accommodate the work, a place to hold exhibitions, entertainment and recreation. But in the city of Pekanbaru did not have a container to realize the activity. The development of photography continues to improve based on the community and photography enthusiasts, so it is a gallery of photography in Pekanbaru. Photographic gallery with a metaphorical architectural approach which has the formation of the camera as a form of building. Meanwhile, the basic concept of building ideas is "Light of Camera", which is lighting inside the camera, where the movement of light in the camera will be applied to the building room.Keywords: Architecture Metafora, Photography, Pekanbaru.